METODE KUANTITATIF DENGAN PENDEKATAN KLASIK PADA APLIKASI ANALISIS BUTIR SOAL SEBAGAI MEDIA EVALUASI PENENTUAN SOAL YANG BERKUALITAS - Redaksi Tim Jurnal (KILAT, 2018)
This paper discusses the design of an application for the analysis on items using quantitative method with the classical approach as a media evaluation for teachers in determining the quality of questions in an exam or a test. The classical approach is the process of examining each item in the test based on the students' answers for calculating the Difficulty Index (Dif I) and the Discrimination Index (DI) of each question. The Difficulty Index is the ratio between the number of students who answered an item (or a question) correctly and the total number of students who participated in the test. The Discrimination Index is a measure of how well an item (or a question) is able to distinguish between clever students and students who are less clever. The data used in this research was obtained from class VII SMPN 10 (Junior High School) Makassar, especially on math (subject). The data includes math questions that have been tested, the answers given bythe students of class VII, and the data about the students. The results of the item analysis will provide information whether a question can be accepted, corrected or to be rejected. The application generated from this research is expected to be able to offer assistance for the teacher in performing item analysis. The results of the analysis can be used to help teachers in compiling more qualified questions in the future.